Impact of Emotional Intelligence on Job Performance —— Examining Mediation and Moderation Mechanisms - Yapeng Lin, Zhongwu Li, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The influence of emotional intelligence on employee job performance has been attracting increasingly more attention from various scholars and enterprises. Based on previous relevant literature in the fields of emotional intelligence, organizational management. This research proposes and verifies a model to examine the internal mechanism and boundary condition of the relationship between emotional intelligence, emotional labor，perceived organizational support，job performance. Specifically, this study introduces emotional labor as a mediator in the relationship between emotional labor and employee job performance and perceived organizational support as a moderator in the relationship between emotional intelligence and emotional labor. Then, this research conducts questionnaire surveys on Chinese employees to collect the sample data. In total, 266 service employees were collected. The results suggest that emotional intelligence can promote employee job performance. Emotional labor can partly mediate the influence of emotional intelligence on employee job performance. perceived organizational support can positively moderate the influence of emotional intelligence on emotional labor. The conclusions from the analyses above not only further verify and develop some previous points on emotional intelligence and employee job performance but also derive certain management implications for promoting employee job performance from the perspective of organizational support.